2012
DOI: 10.5821/ace.v6i18.2546
|View full text |Cite
|
Sign up to set email alerts
|

Anàlisi retrospectiu del sistema metropolità de Barcelona i la seva influència en l’estructura urbana

Abstract: En els últims temps, degut al desbordament dels límits administratius per la urbanització, la literatura ha estudiat vàries aproximacions per delimitar les àrees urbanes i metropolitanes. Simultàniament, aquestes dinàmiques urbanes han donat peu també a l’estructuració de sistemes metropolitans policèntrics, caracteritzats per la dispersió i per la descentralització concentrada de població i ocupació, trencant amb el paradigma de la ciutat monocèntrica. No obstant, pocs estudis s’han concentrat en estudiar din… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A third method is the mobility-based method, which has also been previously applied to Barcelona. This study uses the centers identified by Masip and Roca (2012), who follow the approach of Roca et al (2009) based on identifying centers and delimiting metropolitan areas by examining the functional links between cities.…”
Section: Comparison Of the Outcomes Of Various Methods Of Identifying...mentioning
confidence: 99%
“…A third method is the mobility-based method, which has also been previously applied to Barcelona. This study uses the centers identified by Masip and Roca (2012), who follow the approach of Roca et al (2009) based on identifying centers and delimiting metropolitan areas by examining the functional links between cities.…”
Section: Comparison Of the Outcomes Of Various Methods Of Identifying...mentioning
confidence: 99%
“…A third method is the mobility-based method, which has also been previously applied to Barcelona. This study uses the centers identified by Masip and Roca (2012), who follow the approach of Roca et al (2009) based on identifying centers and delimiting metropolitan areas by examining the functional links between cities.…”
Section: Comparison Of the Outcomes Of Various Methods Of Identifying...mentioning
confidence: 99%